STRATEGIC AWARENESS AND ITS ROLE IN ENHANCING ORGANIZATIONAL AMBIDEXTERITY - Anmar Mudhafar Hadi Mohsen (Scholars Digest Publishing, 2024)
Banks operate in complex, rapidly changing, dynamic environments, so they need a strategic manager or leader who has strategic awareness that enables him to make the right decision at the right time. Organizational ambidexterity is also known as being able to achieve excellence for organizations by exploring and exploiting opportunities, exploring risks, and working to confront them and perhaps benefit from them at times. Organizational ambidexterity also enables one to know the weak points in organizations and work to reduce them and to know the strengths and work to exploit them. Therefore, the idea of this study came from the point of view that strategic awareness will enhance organizational ambidexterity. The problem of this was the study is the answer to the question: Do organizations have strategic awareness that allows them to enhance their organizational ambidexterity? Is there a relationship between strategic awareness and organizational ambidexterity, this study also aims to know the role of strategic awareness in enhancing the organizational prowess of the bank sample of the study. The importance of the study comes from the fact that it deals with the banking sector, as it is considered the main artery of the financial sector. This study assumes that there is a relationship and influence between strategic awareness and organizational prowess, and it has been adopted This study was based on a questionnaire form and (100) valid for the study were distributed and were analyzed through (SPSS.V.26) program. Therefore, this study reached many conclusions, the most important of which is that there is a correlation and influence between strategic awareness and organizational ambidexterity, as strategic awareness It enhances organizational ambidexterity. The study also suggested working to enhance and sustain strategic awareness among employees so that they can achieve organizational ambidexterity that enables them to achieve status and competitive advantage.
Keywords: strategic awareness, organizational ambidexterity.